Setting standard levels for some physical and skill variables for the players in the National Center for the Care of Sports Talent in Volleyball - Khalaf , Naima Zaidan (International Journal of Psychosocial Rehabilitation, 2020)
The research problem lies through the question -What are the standard levels of the most important physical and skill abilities that can appear in the players of specialized centers in volleyball, - What are the physical and skill capabilities that the standards can provide as short variables? - Do these independent variables express us the performance efficiency in competitive situations, That the answer to the above questions can set us standard levels for the most important physical and skill capabilities as indicators for the selection of volleyball players, which helps in achieving a range of benefits for the training process to reach the highest levels and achieve the best achievements. The importance of the research came in determining the most important physical and skill capabilities of volleyball players by setting standard levels in order to find a single standard that can be judged by the performance of the players, in order to stand at the level reached by the player, and thus provide a successful evaluation method according to the scientific methods studied and correct in the evaluation And the selection of players in a transparent manner away from chance, random and bias by coaches, which helps the economy in time, effort and money in order to raise the level of the player in the future, which is the first and necessary stop for the players to reach the important championships in international forums. The research objectives are: Defining some physical and skill variables to evaluate the performance of the National Center for Sports Talent Care in volleyball game at the age of (14-16 years), building normative levels for the most important physical and skill variables for the players of the specialized school in volleyball, and setting themodel for effectiveness (paraffin for effectiveness) The standard levels for the most important variables, physical and skill of volleyball. The researcher used the descriptive method in the survey method to suit the nature of the research and its goals. As for the research community, it represents the players of specialized schools in volleyball, whose number is (60) players, and then the sample was divided into an exploratory and main sample. The researcher reached a number of conclusions: - The best level of physical and skill abilities was distributed at (intermediate) level followed by (good) and then (acceptable) level in the objective evaluation of the talented in the talent centers in volleyball. - The results proved that it is possible to draw a profile map to evaluate and direct the players in the centers of sports talent to the game of volleyball, which is commensurate with its physical and skill capabilities, according to the standard grades and levels reached by the researcher. The researcher recommends: adopting the results that the researcher reached by the talent centers, especially in the selection, evaluation and orientation process, and circulating them in order to adopt them in selecting the qualified players to play volleyball.